Micro Waqf Bank in Indonesia: Some Critical Notes and Solutions - Susamto, Burhanuddin (International Conference on Law, Technology, Spirituality and Society (ICOLESS), 2025)
Micro Waqf Bank (BWM) is the latest model of Islamic microfinance institutions in Indonesia which is expected to eradicate poverty. BWM is a product of popular policy directly relating to the interests of Muslims, especially surroundings of the Islamic boarding school ( pesantren ) community. This study aims to develop the BWM concept in the future because it has great potential for economic empowerment of the poor through the pesantren network. The development of this concept needs to be done because of the fact that there are still weaknesses in the current concept of BWM. Weaknesses at the conceptual level will certainly have an impact on weaknesses at the practical level. From the results of the analysis, we have found that there are eight weaknesses of  BWM  which must be improved and eight solutions that are offered by the authors for the reconstruction of the BWM concept in the future.